2011
DOI: 10.1002/uog.10118
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of intracranial translucency at the 11–13‐week scan is improved after specific training

Abstract: Objective To evaluate the ability to confidently identify intracranial translucency (IT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…Being one of above mentioned markers, absence of intracranial translucency has been suggested to be related to spina bifida, which can be scanned earlier in the first trimester compared to the "lemon" or "banana" sign in the second trimester screening (1-4). Although intracranial translucency measurement is mentioned as reproducible (5,6), it has been shown that specific training increased visualization ratios of intracranial translucency (5). In this study, the retrospective series detection rate was 56-58% versus 91-92% in prospective series, indicating that experience as well as stored planes suitable for NT measurement may not always be suitable for IT visualization (5).…”
Section: Discussionmentioning
confidence: 87%
“…Being one of above mentioned markers, absence of intracranial translucency has been suggested to be related to spina bifida, which can be scanned earlier in the first trimester compared to the "lemon" or "banana" sign in the second trimester screening (1-4). Although intracranial translucency measurement is mentioned as reproducible (5,6), it has been shown that specific training increased visualization ratios of intracranial translucency (5). In this study, the retrospective series detection rate was 56-58% versus 91-92% in prospective series, indicating that experience as well as stored planes suitable for NT measurement may not always be suitable for IT visualization (5).…”
Section: Discussionmentioning
confidence: 87%
“…Although intraobserver and interobserver differences are reported in the manuel measurement of IT, manuel IT measurements are found reproductible [18] . Specific training of the sonographers also improves the visualization rate of IT [19] .…”
Section: Discussionmentioning
confidence: 99%
“…However College Français d'Echographie Foetale (CFEF) has developed a specific score for IT visualization similar to the nuchal translucency using the eight anatomic landmarks: visualization of the thalamus, the midbrain, the brain stem, the posterior wall of the brain stem, the fourth ventricle, the choroid plexus of the fourth ventricle, the spine [19] .…”
Section: Discussionmentioning
confidence: 99%
“…But specifi c training is indispensable if screening using this technique is to be reliable (Fong et al 2011 ;Mangione et al 2011 ).…”
Section: Brain Anomalies Related To Neural Tube Closure Anomaliesmentioning
confidence: 99%